Lithium ion battery negative electrode material and preparation method and application thereof
By using a combination preparation method of silicon precursor material, aqueous alcohol solution, bipolar silane coupling agent and graphite in the lithium-ion battery negative electrode material, a silicon dioxide-coated graphite material is formed, and a core-shell structure negative electrode material is formed through sintering and ball milling treatment, which solves the shortcomings of the existing materials in taking into account high capacity, high first efficiency and high cycle performance, and achieves better battery performance.
Patent Information
- Application Number
- CN202210764471.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-29
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-06-29
AI Technical Summary
Existing graphite or silicon oxygen negative electrode materials are difficult to take into account high capacity, high first-term efficiency and high cycle performance in lithium-ion batteries.
By using a preparation method, a silicon precursor material is mixed with an aqueous solution of alcohol, and an alkaline bipolar silane coupling agent and graphite are added to form a suspension, and then washed, filtered and dried after heating and stirring to obtain a silica-coated graphite material. Then, it is sintered under an inert gas atmosphere, and mixed with aluminum powder of a specific particle size for ball milling to form a lithium-ion battery negative electrode material with a core-shell structure.
This method can improve the battery capacity while improving the first-time efficiency and circulation performance of the battery, solving the shortcomings of existing materials in taking into account high capacity, high-time efficiency and high circulation performance.
Smart Images

Figure CN115117350B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery negative electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development of lithium-ion batteries, high energy density lithium-ion batteries have become one of the performances that consumers and researchers are constantly pursuing. Graphite has a theoretical capacity of 372mAh / g. Due to its low lithium insertion potential, good conductivity, and good cycle stability, it has become the most commonly used negative electrode material among many negative electrode materials. However, although battery design engineers have tried their best to increase the energy density of graphite, they have also reached the limit of graphite's energy density. Therefore, silicon-based negative electrode materials with higher theoretical capacity have gradually been introduced into graphite negative electrodes and have become one of the most promising high energy density negative electrode materials. However, the first efficiency of silicon-based negative electrode materials is low, and the capacity decay is serious during the cycle, which limits their practical application.
[0003] The existing methods for improving graphite or silicon oxide negative electrode materials are mainly carried out in the following ways: (1) physical mixing; (2) bonding through asphalt, resin or polymer after material mixing, and then sintering into amorphous carbon for use; (3) coating the surface of silicon oxide negative electrode with graphite for use. However, when the negative electrode materials obtained by the existing modification methods are applied to lithium-ion batteries, it is not possible to effectively ensure that the battery has high capacity and excellent initial efficiency and cycle performance. Summary of the invention
[0004] In order to overcome the defects of existing graphite or silicon oxide negative electrode materials that cannot achieve high capacity, high initial efficiency and high cycle performance, a lithium ion battery negative electrode material and a preparation method and application thereof are provided.
[0005] In order to achieve the above object, the present invention adopts the following technical scheme:
[0006] A method for preparing a negative electrode material for a lithium ion battery comprises the following steps:
[0007] 1) mixing a silicon precursor material and an alcohol aqueous solution, and stirring to obtain a mixed solution;
[0008] 2) mixing an alkaline bipolar silane coupling agent, water and graphite, and stirring to obtain a suspension;
[0009] 3) adding the suspension obtained in step 2) dropwise to the mixed solution in step 1), heating and stirring, washing, filtering, and drying to obtain a silica-coated graphite material;
[0010] 4) sintering the silicon dioxide-coated graphite material under an inert gas atmosphere, and sieving to obtain a sintered product;
[0011] 5) The sintered product is mixed with aluminum powder with a particle size of 50-100 nm and then ball-milled to obtain the negative electrode material for the lithium-ion battery.
[0012] Preferably,
[0013] The mass ratio of the silicon precursor material to the alcohol aqueous solution is (0.05-3):100, for example, 0.1:100, 0.3:100, 0.6:100, 0.8:100, 1:100, 1.5:100, 1.8:100, 2.0:100. Preferably, the mass ratio of the silicon precursor material to the alcohol aqueous solution is (0.1-1):100, further preferably, (0.1-0.5):100;
[0014] The mass ratio of alcohol to water in the alcohol aqueous solution is (4-12):100, such as 4:100, 4.5:100, 6:100, 7:100, 7.5:100, 8:100, 9:100, 12:100. Preferably, the mass ratio of alcohol to water in the alcohol aqueous solution is (4-10):100. More preferably, the mass ratio of alcohol to water in the alcohol aqueous solution is (4-6):100.
[0015] The mass ratio of the bipolar silane coupling agent to water is (0.2-4):100, for example, 0.2:100, 0.5:100, 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 4:100; the mass ratio of the bipolar silane coupling agent to water is (0.5-2):100; the mass ratio of the bipolar silane coupling agent to water is (0.5-1):100;
[0016] The mass ratio of the bipolar silane coupling agent to graphite is (0.1-5):1;
[0017] The mass ratio of the suspension and the mixed solution in step 3) is (0.5-2):1;
[0018] After the heating and stirring in step 3), the method further comprises a filtering step.
[0019] Preferably,
[0020] The present invention does not specifically limit the type of silicon precursor material, which includes but is not limited to methyl orthosilicate, ethyl orthosilicate, and propyl orthosilicate. Preferably, the silicon precursor material is selected from at least one of methyl orthosilicate, ethyl orthosilicate, and propyl orthosilicate. Preferably, the silicon precursor material is selected from methyl orthosilicate;
[0021] The alcohol in the aqueous solution of alcohol in the present invention may be a long-chain or short-chain hydrocarbon organic alcohol. Preferably, the aqueous solution of alcohol is selected from at least one of a methanol aqueous solution, an ethanol aqueous solution, and a propanol aqueous solution. Preferably, the aqueous solution of alcohol is selected from a methanol aqueous solution.
[0022] The alkaline bipolar silane coupling agent is selected from one or more of γ-aminopropyltriethoxysilane (KH550), vinyltriethoxysilane (A151), vinyltrimethoxysilane (A171), and vinyltri(β-methoxyethoxy)silane (A172). Preferably, the alkaline bipolar silane coupling agent is γ-aminopropyltriethoxysilane.
[0023] The graphite is selected from at least one of natural graphite and artificial graphite.
[0024] Preferably,
[0025] In step 3), the heating and stirring temperature is 30-80°C, and the heating and stirring time is 4-24h. Preferably, the heating and stirring temperature is 30-60°C, and the heating and stirring time is 6-18h. More preferably, the heating and stirring temperature is 30-50°C, and the heating and stirring time is 8-12h.
[0026] The washing step in step 3) is performed with an alcohol aqueous solution, the drying temperature is 60-80°C, the drying time is 6-12h, preferably, the drying temperature is 60°C, and the drying time is 8h. Preferably, the alcohol aqueous solution is selected from at least one of a methanol aqueous solution, an ethanol aqueous solution, and a propanol aqueous solution, and the mass ratio of alcohol to water in the alcohol aqueous solution is (4-12): 100; preferably, the washing times are 2-8 times.
[0027] In step 4), the sintering temperature is 800-1200° C., the sintering time is 2-6 hours, and the sieve mesh is 320-330 mesh;
[0028] Preferably, in step 5), the molar ratio of silicon element to aluminum powder in the sintered product is 1:(0.1-0.6); preferably, the molar ratio of silicon element to aluminum powder in the sintered product is 1:(0.2-0.4);
[0029] The ball milling speed is 800-1200 rpm, and the ball milling time is 6-10 h. Preferably, the ball milling speed is 800-1000 rpm, and the ball milling time is 6-8 h.
[0030] The mass ratio of ball to material in the ball milling step is (10-20):1. It can be understood that the ball in the ball material of the present invention refers to the grinding ball, and the material refers to the sintered product and the aluminum powder mixed material.
[0031] Preferably,
[0032] The sintering temperature in step 4) is 900-1100°C, and the sintering time is 2-4h. During the sintering process, the present invention does not specifically limit the heating rate and the cooling rate. Optionally, the heating rate can be 3°C to 5°C / min, and the cooling rate can be 3°C to 5°C / min.
[0033] The particle size of the aluminum powder is 50-80nm;
[0034] The inert gas is selected from argon and nitrogen.
[0035] The present invention also provides a lithium ion battery negative electrode material, which is prepared by the above-mentioned preparation method.
[0036] Preferably, the negative electrode material of the lithium-ion battery has a core-shell structure, wherein the core material is graphite, and the shell material coated on the surface of the graphite is metal aluminum-doped silicon oxide. The metal aluminum-doped silicon oxide can be SiAl x O means, 0.1 <x<0.6。
[0037] The present invention also provides a lithium ion battery negative electrode sheet, which contains the above-mentioned lithium ion battery negative electrode material.
[0038] The present invention also provides a lithium ion battery comprising the above-mentioned lithium ion battery negative electrode sheet.
[0039] Beneficial effects of the present invention:
[0040] 1. The preparation method of the negative electrode material of a lithium ion battery provided by the present invention comprises the following steps: mixing a silicon precursor material and an aqueous solution of an alcohol, stirring to obtain a mixed solution; mixing an alkaline bipolar silane coupling agent, water and graphite, stirring to obtain a suspension; dropping the suspension into the mixed solution, heating and stirring, washing, filtering and drying to obtain a silicon dioxide-coated graphite material; sintering the silicon dioxide-coated graphite material under an inert gas atmosphere, sieving to obtain a sintered product; mixing the sintered product with aluminum powder with a particle size of 50-100 nm and then ball milling to obtain the negative electrode material of the lithium ion battery.
[0041] The present invention firstly hydrolyzes and condenses a silicon precursor material through an alcohol aqueous solution to form a mixed solution, mixes an alkaline bipolar silane coupling agent, water and graphite to form a suspension, then drops the suspension into the mixed solution, heats and stirs, washes, filters and dries to obtain a silicon dioxide-coated graphite material (graphite @ SiO2), and sinters the silicon dioxide-coated graphite material in an inert gas atmosphere and sieves it. The sintered product is mixed with 50-100nm aluminum powder and then ball-milled. During the ball-milling process, Al competes for oxygen atoms in silicon dioxide, and under the action of ball-milling, Al-doped silicon dioxide shell structure material SiAl is formed. x O. The present invention uses an alkaline bipolar silane coupling agent as a catalyst, which can not only catalyze the polycondensation of silicon precursor materials to form SiO2, but also modify the graphite surface, enhance the hydrophilicity of graphite in the solution, and promote the formation of a uniform SiO2 coating layer on the graphite surface. In an inert gas atmosphere, the sintered product is ball-milled with nano-aluminum powder of a specific particle size. During the high-energy ball milling process, Al will compete for oxygen atoms in silicon dioxide to form Al-doped silicon oxide shell structure materials, which can effectively inhibit silicon oxygen expansion, improve graphite wettability, and improve mechanical properties. The lithium ion battery negative electrode material prepared by the present invention has a core-shell structure, wherein the core material is graphite, and the shell material coated on the graphite surface is metal aluminum-doped silicon oxide. The application of the negative electrode material in lithium ion batteries can improve the battery capacity while improving the first efficiency and cycle performance of the battery.
[0042] In addition, the preparation method provided by the present invention is simple and easy to operate, with uniform liquid phase coating and solid phase doping, and uniform coating and doping of silicon aluminum oxide on the graphite surface, which simplifies the process of graphite and silicon oxygen composite and doping, realizes both the composite of silicon oxide and graphite and the doping of Al element, takes into account the capacity of graphite and silicon oxygen negative electrode and the advantages of Al element doping to reduce silicon negative electrode expansion, modify graphite interface, and enhance material surface wettability, thereby obtaining a negative electrode material with high energy and long cycle performance.
[0043] 2. The preparation method of the negative electrode material of a lithium ion battery provided by the present invention, further, the alkaline bipolar silane coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, and vinyltri(β-methoxyethoxy)silane, and preferably, the alkaline bipolar silane coupling agent is γ-aminopropyltriethoxysilane; the present invention adopts a specific silane coupling agent that has the function of coupling organic and inorganic substances, which can not only polarize graphite to enhance the hydrophilicity of graphite, but also facilitate the dispersion of graphite in water to form a uniform suspension, and the alkaline coupling agent can catalyze the hydrolysis and condensation of the silicon precursor material to form SiO2, and can make SiO2 couple with graphite and grow on the surface of graphite, uniformly coating the surface of graphite, and after subsequent sintering and ball milling with aluminum powder, it is beneficial to improve the battery capacity, first efficiency and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0045] Figure 1 This is a schematic diagram of the structure of the negative electrode material for a lithium-ion battery prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0046] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0047] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0048] Example 1
[0049] This embodiment provides a method for preparing a negative electrode material for a lithium ion battery, comprising the following steps:
[0050] 1) adding 0.5 g of methyl orthosilicate into 100 g of methanol aqueous solution (the mass ratio of methanol to water in the methanol aqueous solution is 4:100), stirring with a magnetic stirrer until uniform, to form a mixed solution;
[0051] 2) Add 0.5 g KH550 to 100 g ultrapure water, stir with a mechanical stirrer until uniform, then add 1 g natural graphite, stir to obtain a suspension;
[0052] 3) adding the suspension obtained in step 2) dropwise into the mixed solution of step 1), heating and stirring at 30° C. for 8 h, filtering after the stirring, washing the product with a methanol aqueous solution (the mass ratio of methanol to water in the methanol aqueous solution is 4:100) for 6 times, filtering with suction, and drying the filter cake at 60° C. for 8 h to obtain a silica-coated graphite material;
[0053] 4) placing the silica-coated graphite material obtained in step 3) into a crucible, and sintering it in a high-temperature tube furnace under an argon atmosphere, with a heating rate of 3°C / min, a sintering temperature of 900°C, and a sintering time of 3h. After sintering, the temperature is lowered to room temperature at a rate of 3°C / min, and the material is sieved through a 325-mesh sieve to obtain a sintered product;
[0054] 5) 1.18g of the sintered product (the silicon content in the sintered product is 0.003mol) and aluminum powder with a particle size of 50 nanometers (the molar ratio of silicon to aluminum powder in the sintered product is 1:0.3) are placed in a ball mill, zirconium oxide beads are added, and the ball-to-material mass ratio is 20:1. The ball milling is performed at a speed of 800rpm for 8h, and the ball milling product is sieved to obtain the lithium ion battery negative electrode material. The lithium ion battery negative electrode material prepared by the above method has a core-shell structure, wherein the core material is graphite, and the shell material coated on the graphite surface is metal aluminum-doped silicon oxide.
[0055] Example 2
[0056] This embodiment provides a method for preparing a negative electrode material for a lithium ion battery, comprising the following steps:
[0057] 1) adding 0.5 g of methyl orthosilicate into 100 g of methanol aqueous solution (the mass ratio of methanol to water in the methanol aqueous solution is 4:100), stirring with a magnetic stirrer until uniform, to form a mixed solution;
[0058] 2) Add 4 g KH550 to 100 g ultrapure water, stir with a mechanical stirrer until uniform, then add 1 g natural graphite, stir to obtain a suspension;
[0059] 3) adding the suspension obtained in step 2) dropwise into the mixed solution of step 1), heating and stirring at 30° C. for 8 h, filtering after the stirring, washing the product with methanol aqueous solution (the mass ratio of methanol to water in the methanol aqueous solution is 4:100) for 7 times, filtering with suction, and drying the filter cake at 60° C. for 6 h to obtain a silica-coated graphite material;
[0060] 4) placing the silica-coated graphite material obtained in step 3) into a crucible, and sintering it in a high-temperature tube furnace under an argon atmosphere, with a heating rate of 3°C / min, a sintering temperature of 900°C, and a sintering time of 4h. After sintering, the temperature is lowered to room temperature at a rate of 3°C / min, and the material is sieved through a 325-mesh sieve to obtain a sintered product;
[0061] 5) 1.18g of the sintered product (the silicon content in the sintered product is 0.003mol) and aluminum powder with a particle size of 50 nanometers (the molar ratio of silicon to aluminum powder in the sintered product is 1:0.3) are placed in a ball mill, zirconium oxide beads are added, and the ball-to-material mass ratio is 20:1. The ball milling is performed at a speed of 800rpm for 8h, and the ball milling product is sieved to obtain the lithium ion battery negative electrode material. The lithium ion battery negative electrode material prepared by the above method has a core-shell structure, wherein the core material is graphite, and the shell material coated on the graphite surface is metal aluminum-doped silicon oxide.
[0062] Example 3
[0063] This embodiment provides a method for preparing a negative electrode material for a lithium ion battery, comprising the following steps:
[0064] 1) 3 g of methyl orthosilicate was added to 100 g of methanol aqueous solution (the mass ratio of methanol to water in the methanol aqueous solution was 4:100), and stirred with a magnetic stirrer until uniform to form a mixed solution;
[0065] 2) Add 0.5 g KH550 to 100 g ultrapure water, stir with a mechanical stirrer until uniform, then add 1 g natural graphite, stir to obtain a suspension;
[0066] 3) adding the suspension obtained in step 2) dropwise into the mixed solution of step 1), heating and stirring at 30° C. for 8 h, filtering after the stirring, washing the product with methanol aqueous solution (the mass ratio of methanol to water in the methanol aqueous solution is 4:100) for 7 times, filtering with suction, and drying the filter cake at 70° C. for 8 h to obtain a silica-coated graphite material;
[0067] 4) placing the silica-coated graphite material obtained in step 3) into a crucible, and sintering it in a high-temperature tube furnace under an argon atmosphere, with a heating rate of 3°C / min, a sintering temperature of 900°C, and a sintering time of 3h. After sintering, the temperature is lowered to room temperature at a rate of 3°C / min, and the material is sieved through a 325-mesh sieve to obtain a sintered product;
[0068] 5) 2.18 g of the sintered product (the silicon content in the sintered product is 0.019 mol) and aluminum powder with a particle size of 50 nanometers (the molar ratio of silicon to aluminum powder in the sintered product is 1:0.5) are placed in a ball mill, zirconium oxide beads are added, and the ball-to-material mass ratio is 15:1. The ball milling is performed at a speed of 800 rpm for 8 hours, and the ball milling product is sieved to obtain the lithium ion battery negative electrode material. The lithium ion battery negative electrode material prepared by the above method has a core-shell structure, wherein the core material is graphite, and the shell material coated on the graphite surface is metal aluminum-doped silicon oxide.
[0069] Example 4
[0070] This embodiment provides a method for preparing a negative electrode material for a lithium ion battery, comprising the following steps:
[0071] 1) 0.1 g of tetraethyl orthosilicate was added to 100 g of methanol aqueous solution (the mass ratio of methanol to water in the methanol aqueous solution was 12:100), and stirred with a magnetic stirrer until uniform to form a mixed solution;
[0072] 2) adding 4 g of vinyltrimethoxysilane to 100 g of ultrapure water, stirring with a mechanical stirrer until uniform, then adding 1 g of artificial graphite, stirring to obtain a suspension;
[0073] 3) adding the suspension obtained in step 2) dropwise into the mixed solution of step 1), heating and stirring at 60° C. for 4 h, filtering after the stirring, washing the product with a methanol aqueous solution (the mass ratio of methanol to water in the methanol aqueous solution is 5:100) for 6 times, filtering with suction, and drying the filter cake with air at 70° C. for 10 h to obtain a silica-coated graphite material;
[0074] 4) placing the silica-coated graphite material obtained in step 3) into a crucible, and sintering it in a high-temperature tube furnace under an argon atmosphere, with a heating rate of 4°C / min, a sintering temperature of 800°C, and a sintering time of 6h. After sintering, the temperature is lowered to room temperature at a rate of 4°C / min, and the material is sieved through a 325-mesh sieve to obtain a sintered product;
[0075] 5) 1.029g of the sintered product (the silicon content in the sintered product is 0.00048mol) and aluminum powder with a particle size of 100nm (the molar ratio of silicon to aluminum powder in the sintered product is 1:0.6) are placed in a ball mill, zirconium oxide beads are added, and the ball-to-material mass ratio is 20:1. The ball milling is carried out at a speed of 1000rpm for 10h, and the ball milling product is sieved to obtain the lithium ion battery negative electrode material. The lithium ion battery negative electrode material prepared by the above method has a core-shell structure, wherein the core material is graphite, and the shell material coated on the graphite surface is metal aluminum-doped silicon oxide.
[0076] Example 5
[0077] This embodiment provides a method for preparing a negative electrode material for a lithium ion battery, comprising the following steps:
[0078] 1) 2 g of methyl orthosilicate was added to 100 g of methanol aqueous solution (the mass ratio of methanol to water in the methanol aqueous solution was 10:100), and stirred with a magnetic stirrer until uniform to form a mixed solution;
[0079] 2) adding 2 g of vinyl triethoxysilane to 100 g of ultrapure water, stirring with a mechanical stirrer until uniform, then adding 1 g of natural graphite, stirring to obtain a suspension;
[0080] 3) adding the suspension obtained in step 2) dropwise into the mixed solution of step 1), heating and stirring at 50° C. for 8 h, filtering after the stirring, washing the product with a methanol aqueous solution (the mass ratio of methanol to water in the methanol aqueous solution is 10:100) for 6 times, filtering with suction, and drying the filter cake at 70° C. for 12 h to obtain a silica-coated graphite material;
[0081] 4) placing the silica-coated graphite material obtained in step 3) into a crucible, and sintering it in a high-temperature tube furnace under an argon atmosphere, with a heating rate of 4°C / min, a sintering temperature of 1200°C, and a sintering time of 2h. After sintering, the temperature is lowered to room temperature at a rate of 4°C / min, and the material is sieved through a 325-mesh sieve to obtain a sintered product;
[0082] 5) 1.78g of the sintered product (the silicon content in the sintered product is 0.013mol) and aluminum powder with a particle size of 60 nanometers (the molar ratio of silicon to aluminum powder in the sintered product is 1:0.2) are placed in a ball mill, zirconium oxide beads are added, and the ball-to-material mass ratio is 20:1. The ball milling is performed at a speed of 1200rpm for 6h, and the ball milling product is sieved to obtain the lithium ion battery negative electrode material. The lithium ion battery negative electrode material prepared by the above method has a core-shell structure, wherein the core material is graphite, and the shell material coated on the graphite surface is metal aluminum-doped silicon oxide.
[0083] Comparative Example 1
[0084] This comparative example provides a method for preparing a negative electrode material for a lithium ion battery, which differs from Example 1 in that in step 5), the aluminum powder with a particle size of 50 nanometers is replaced with aluminum powder with a particle size of 500 nanometers.
[0085] Comparative Example 2
[0086] This comparative example provides a method for preparing a negative electrode material for a lithium ion battery, which differs from Example 1 in that in step 2), KH550 is replaced by ammonia water with a mass concentration of 30%.
[0087] Comparative Example 3
[0088] This comparative example provides a method for preparing a negative electrode material for a lithium ion battery, comprising the following steps: mixing 1 g of natural graphite and 0.17 g of silicon oxide to obtain the negative electrode material for a lithium ion battery.
[0089] Comparative Example 4
[0090] This comparative example provides a method for preparing a negative electrode material for a lithium ion battery, which differs from Example 1 in that in step 5), 1.18 g of a sintered product (the silicon content in the sintered product is 0.003 mol) is placed in a ball mill, zirconium oxide beads are added, the ball-to-material mass ratio is 20:1, the product is ball milled at a speed of 800 rpm for 8 hours, and the ball milled product is sieved to obtain the negative electrode material for a lithium ion battery.
[0091] Test Case
[0092] Button half-cell production process:
[0093] 1) Preparation of electrolyte
[0094] Dissolve an equal volume of ethylene carbonate in ethyl methyl carbonate, and then evenly dissolve an appropriate amount of LiPF6 in the mixed solvent to form a 1 mol / L electrolyte for use.
[0095] 2) Negative electrode
[0096] The negative electrode material prepared in the embodiment or comparative example, styrene-butadiene rubber, sodium carboxymethyl cellulose and conductive agent Super P (superconducting carbon black) were mixed in a mass ratio of 95wt%:2.2wt%:1.8wt%:1wt%, and homogenized with deionized water. The prepared slurry was evenly coated on a 6μm thick copper foil, and the single-sided coating weight was 8.5mg / cm 2 , and then dried, rolled, and punched into negative electrode discs with a diameter of 14 mm.
[0097] 3) Isolation film: PP material isolation film with a thickness of 16μm is used.
[0098] 4) Battery assembly:
[0099] Stack the CR2032 negative electrode battery shell, spring, gasket, lithium sheet, electrolyte, diaphragm, negative electrode disc, and positive electrode shell in sequence, seal them with a sealing machine, and let them stand for 12 hours before conducting a performance test.
[0100] The electrochemical performance tests of the batteries prepared above were carried out respectively, as follows:
[0101] The test method of 0.1C initial discharge capacity is as follows: discharge at 0.1C rate to 5mV, 0.05C rate to 5mV, 0.02C rate to 5mV, 0.01C rate to 5mV (the total discharge capacity is recorded as the negative electrode first lithium insertion capacity C0), and leave it for 20min; charge at 0.1C rate to 2V (record the charging capacity as the negative electrode delithiation capacity C0 of 0.1C). t ), and calculate the first charge and discharge efficiency (first efficiency), first charge and discharge efficiency / % = (C t / C0)*100%.
[0102] The test method of capacity retention rate is as follows: discharge at 0.1C rate to 5mV, 0.05C rate to 5mV, 0.02C rate to 5mV, 0.01C rate to 5mV, and leave for 20min; charge at 0.1C rate to 2V (record the negative electrode delithiation capacity C1 of 0.1C charging capacity), cycle 50 times and record the charging capacity C 50 ; Capacity retention rate / % = (C 50 / C1)*100%.
[0103] The test results are shown in Table 1.
[0104]
[0105]
[0106] It can be seen from Table 1 that the capacity, first efficiency and cycle performance of the battery of the negative electrode material in the embodiment of the present invention are improved compared with the comparative example. It can be seen that the present invention uses a specific alkaline bipolar silane coupling agent as a catalyst and uses nano-aluminum powder with a specific particle size as a doping material to simultaneously improve the capacity, first efficiency and cycle performance of the battery.
[0107] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a negative electrode material for a lithium ion battery, characterized in that: The steps include: 1) mixing a silicon precursor material and an alcohol aqueous solution, and stirring to obtain a mixed solution; 2) mixing an alkaline bipolar silane coupling agent, water and graphite, and stirring to obtain a suspension; 3) adding the suspension obtained in step 2) dropwise to the mixed solution in step 1), heating and stirring, washing, filtering, and drying to obtain a silica-coated graphite material; 4) sintering the silicon dioxide-coated graphite material under an inert gas atmosphere, and sieving to obtain a sintered product; 5) The sintered product is mixed with aluminum powder with a particle size of 50-100 nm and then ball-milled to obtain the negative electrode material for the lithium-ion battery.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the silicon precursor material to the alcohol aqueous solution is (0.05-3):100; The mass ratio of alcohol to water in the alcohol aqueous solution is (4-12):100; The mass ratio of the bipolar silane coupling agent to water is (0.2-4):100; The mass ratio of the bipolar silane coupling agent to graphite is (0.1-5):1; The mass ratio of the suspension to the mixed solution in step 3) is (0.5-2):
1.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the silicon precursor material to the alcohol aqueous solution is (0.1-1):
100.
4. The preparation method according to claim 1, characterized in that: The mass ratio of alcohol to water in the alcohol aqueous solution is (4-10):
100.
5. The preparation method according to claim 1, characterized in that: The mass ratio of alcohol to water in the alcohol aqueous solution is (4-6):
100.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the bipolar silane coupling agent to water is (0.5-2):
100.
7. The preparation method according to claim 1, characterized in that: The mass ratio of the bipolar silane coupling agent to water is (0.5-1):
100.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The silicon precursor material is selected from at least one of methyl orthosilicate, ethyl orthosilicate and propyl orthosilicate; The alcohol aqueous solution is selected from at least one of a methanol aqueous solution, an ethanol aqueous solution, and a propanol aqueous solution; The alkaline bipolar silane coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, and vinyltri(β-methoxyethoxy)silane. The graphite is selected from at least one of natural graphite and artificial graphite.
9. The preparation method according to claim 1, characterized in that: The silicon precursor material is selected from methyl orthosilicate.
10. The preparation method according to claim 1, characterized in that: The aqueous alcohol solution is selected from aqueous methanol solution.
11. The preparation method according to claim 1, characterized in that: The alkaline bipolar silane coupling agent is γ-aminopropyltriethoxysilane.
12. The preparation method according to claim 1, characterized in that: The heating and stirring temperature in step 3) is 30-80°C, and the heating and stirring time is 4-24h; The washing step in step 3) is performed with an alcohol aqueous solution, the drying temperature is 60-80° C., and the drying time is 6-12 hours; In step 4), the sintering temperature is 800-1200° C., the sintering time is 2-6 hours, and the sieve mesh number is 320-330 meshes.
13. The preparation method according to claim 1, characterized in that: The heating and stirring temperature in step 3) is 30-60°C, and the heating and stirring time is 6-18h.
14. The preparation method according to claim 1, characterized in that: The heating and stirring temperature in step 3) is 30-50°C, and the heating and stirring time is 8-12h.
15. The preparation method according to claim 1, characterized in that: In step 5), the molar ratio of silicon element to aluminum powder in the sintered product is 1:(0.1-0.6); The ball milling speed is 800-1200 rpm, and the ball milling time is 6-10 h; The mass ratio of balls to materials in the ball milling step is (10-20):
1.
16. The preparation method according to claim 1, characterized in that: In step 5), the molar ratio of silicon element to aluminum powder in the sintered product is 1:(0.2-0.4).
17. The preparation method according to claim 1, characterized in that: In step 5), the ball milling speed is 800-1000 rpm, and the ball milling time is 6-8 h.
18. The preparation method according to claim 1, characterized in that: In step 4), the sintering temperature is 900-1100° C. and the sintering time is 2-4 hours; The particle size of the aluminum powder is 50-80nm; The inert gas is selected from argon and nitrogen.
19. A negative electrode material for a lithium ion battery, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 18.
20. The negative electrode material for lithium-ion batteries according to claim 19, characterized in that: The negative electrode material of the lithium ion battery has a core-shell structure, wherein the core material is graphite, and the shell material coated on the surface of the graphite is silicon oxide doped with metal aluminum.
21. A negative electrode sheet for a lithium ion battery, characterized in that: Contains the lithium ion battery negative electrode material according to claim 19 or 20.
22. A lithium ion battery, characterized in that: A lithium-ion battery negative electrode sheet comprising the negative electrode sheet of claim 21.
Citation Information
Patent Citations
Method for preparing silicon-based composite anode material of lithium ion battery
CN104681798A
Method for preparing lithium ion cathode high-capacity composite material
CN108807870A